HISTORICAL AND GEOPOLITICAL SIGNIFICANCE OF THE BATTLE OF KOŠARE IN 1999 - Suljagic, Sanja (Political Review, 2025)
In this paper, author presented historical and geopolitical factors which influenced that the NATO alliance to begin its aggression against the-then Federal Republic of Yugoslavia (Serbia and Crna Gora) in the spring of 1999, as well as historical significance of defense of the border of Kosovo and Metohija for Serbian people in this period and in general оverview of Serbian history. The focus of the research is historical and geopolitical circumstances before, during, and after the NATO aggression against the Federal Republic of Yugoslavia, with special consideration being given to the signing of the Military-Technical Agreement at a military airport near Kumanovo town (so-called Kumanovo Agreement) by the two sides on June 9th, 1999. Then, by the use of analytical-synthetic and comparative methods, political and economic circumstances in the aftermath of the Battle of Košare and the consequences of the Battle for its participants in the Army of Yugoslavia, later the Army of Serbia, are analyzed. The objective of the research was to understand the impact of the Battle of Košare on the continuity of identity of Serbian people at the turn of the 20th and 21st centuries. Results of the research show that the way by which representatives of the state institutions, artists, political analysts and in particular politicasters among them, and the Serbian people in general related to the remembrance of the Battle of Košare reflects a great significance of this Battle for the (dis)continuity of Serbian people and state in future.
Keywords: Kosovo and Metohija; NATO aggression against FR Yugoslavia; battle of Košare; Kumanovo Agreement